Factors influencing vancomycin trough concentration in burn patients: a single center retrospective study - Shi, Yan; Yin, Zongqi; Zhang, Qin; Yi, Lei; Dou, Yi (Frontiers in Pharmacology, 2024)
ObjectiveTo analyze factors influencing the vancomycin trough concentration in burn patients to provide a basis for the more rational use of vancomycin in these patients.Materials and methodsWe collected the clinical data of adult burn patients treated with vancomycin in a Chinese hospital. Vancomycin was administered at a dosing regimen of 1.0 g q12 h. Patients were divided into a therapeutic group with vancomycin trough concentration in the target therapeutic range (10–20 μg/mL) and a subtherapeutic group with vancomycin trough concentration in the subtherapeutic range (<10 μg/mL).ResultsThe therapeutic group included 14 patients (17.5%), with an average trough concentration of 14.36 ± 2.82 μg/mL; the subtherapeutic group included 66 patients (82.5%), with an average trough concentration of 5.18 ± 2.77 μg/mL. The serum creatinine level was significantly higher in the therapeutic group (84.93 ± 47.26 μmol/L) than that in the subtherapeutic group (62.44 ± 14.49 μmol/L) (p < 0.01). Serum albumin levels were significantly lower in the therapeutic group (30.50 ± 2.28 g/L) than those in the subtherapeutic group (34.00 ± 6.22 g/L) (p < 0.05). Using receiver operating characteristic (ROC) curve analysis, for serum albumin, the area under the ROC curve (AUC) (95% confidence interval [CI]) was 0.67 (0.553, 0.788); the optimal cut-off point was 34.50 g/L (p = 0.046), the sensitivity was 0.379, and the specificity was 1.0. For creatinine clearance, the AUC (95% CI) was 0.72 (0.537, 0.902); the optimal cut-off point was 76.64 mL/min (p = 0.01), the sensitivity was 0.985, and the specificity was 0.5. The linear stepwise regression equation was as follows: trough concentration = 0.14 × age + 0.071 × serum creatinine −4.196.ConclusionIn this study, a high proportion of burn patients had a vancomycin trough concentration below the standard range. Serum creatinine clearance and albumin levels are important indicators for predicting whether the vancomycin trough concentration is within the standard range. Using a linear stepwise regression equation, the vancomycin trough concentration can be estimated using the patient’s age and serum creatinine level.